Distribution development strategy of corn processed (corn stick and corn dodol) production to achieve corn competitive product market in Gorontalo Province - Amir Halid; Mohammad Ikbal Bahuwa; Zainudin K Antuli; Irawati Abdul (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2017)
Reseach object are; 1) to know about the profile of maize farmer enterprise in Gorontalo Regency; 2) to know the people characteristic at home industry group in Todito village at Pulubala sub-district; 3) Economics analysis for Sweat Maize Dodol. Data analysis used is descriptive method, SWOT and economics analysis. The result of this research is 1) Groups of farmers enterprise, the more much of members and land is worked on by maize farmer found at Dunggala village in Batudaa sub-district. At Pulubala Sub-district the more much of groups of farmer enterprise at Puncak Village, and the members is more much found at Toidito, but the largest land worked on by maize farmer is at Puncak village; 2) Production analysis for home industry for Maize Stick with tasted by Shrimp from Llimboto Lake will get profit if the income above of break event is Rp 120.000,- if production is over of break even point is 11,975 gram and will follow of the price over of break even point about Rp 52.500. Production analysis for home industry for Dodol sweat maize will get profit if the income earned over of break even point is Rp 170,174, if production is earned over of break even point 6,90 basket and if the price is over of break even point is about 19.550; 4) Main distribution development strategy of corn stick and corn dodol are developing corn distribution product, increased the volume of production, to reach the market target, and increased the promotion of product and price information. Key words: Corn Production, Distribution Development Strategy AbstrakPenelitian ini bertujuan untuk; 1) Mengetahui profil petani jagung di Kabupaten Gorontalo; 2) Mengetahui karakteristik pelaku industri rumah tangga di Desa Todito, Kecamatan Pulubala; 3) Analisis ekonomi dodol jagung manis. Analisis data menggunakan analisis deskriptif, SWOT, dan analisis ekonomi. Hasil peneltian: 1) Kelompok, jumlah anggota dan luas tanaman jagung terbanyak di Kecamatan Batudaa terdapat di Desa Dunggala. Di Kecamatan Pulubala kelompok petani jagung terbanyak dan lahan terluas terdapat di Desa Puncak, dan jumlah anggota kelompok terbanyak terdapat di Desa Toidito; 2) Keuntungan industri stik jagung rasa udang di Danau Limboto dengan pendapatan di atas BEP (Break Even Point) sebesar Rp. 120.000,- dengan BEP produksi sebesar 11,975 gram dan BEP harga Rp. 52.500. Keuntungan industri dodol jagung manis dengan pendapatan di atas BEP sebesar 170,174, dengan BEP produksi sebesar 6,90 keranjang, dan BEP harga sebesar 19.550. 3) Strategi utama pengembangan distribusi stik jagung dan dodol jagung adalah mengembangkan produk distribusi jagung, meningkatkan volume produksi, untuk mencapai target pasar, dan meningkatkan promosi produk dan informasi harga. Kata Kunci: Produksi Jagung, Strategi Pengembangan Distribusi REFERENCESAhmad, Lisna. 2011 dan 2012.Analisis sifat fisiokimia dan respon konsumen terhadap tepung pudding instan hasil formula siteping jagung dan karagenan. Laporan Penelitian. Gorontalo: Lemlit UNG.Ahmad, Lisna. 2013. Kajian dan pengembangan crackers nike hasil formulasi tepung jagung dan ikan nike. Laporan Penelitian. Gorontalo: Lemlit UNG.Muhammad, Fadel. 2012. Indonesia effortstowards the leading of maize agribusiness and agroindustry in the world by 2025. Paparan disampaikan pada International Maize Conference. Gorontalo 22-24 November 2012.Friedman, John. 1990. Empowerment: the politics of alternative development (Cambridge MA & Oxford UK: Blaekwell, 1982Halid, Amir. 2010. Dampak agropolitan jagung terhadap penurunan angka kemiskinan di Kabupaten Gorontalo;.Laporan PenelitianHalid, Amir, 2014. Pengembangan profitabilitas jagung, Idaes Publishing, Gorontalo.Halid, Amir, M.I. Bahua, Z. K. Antuli. I. Abdul 2016 Maize processing production development as the economic driven of people in Gorontalo Province. Cnference On Proceedings Malaysia Indonesia International Conference on Economic, Management and Accounting (MIICEMA) 2016, ISBN 978-602-98081-4-8Hasan, M. Ani. 2011. Aktualisasi program pemberdayaan masyarakat pedesaan guna peningkatan pertumbuhan ekonomi daerah dalam rangka ketahanan nasional. Laporan Penelitian.Hasan, A.M., R. Ilato, A. Halid dan L. Ahmad. 2016. Farmer empowerment through prcessing of maize and each waste in to productive economic comodity in Boalemo Regency of Gorontalo. International Journal of Bussiness, Accounting and Management. Vol.1 Issue 3. ISSN 2527-3531: 53-64Hatu, Rauf . 2010. Pemberdayaan dan pendampingan sosial masyarakat. Gorontalo: Jurnal inovasi.Ibrahim, Amin. 2009. Pokok-pokok administrasi publik dan implementasinya. Bandung: Refika AditamaIlato, Rosman dan Bahua, M. Ikbal. 2013. Analisis rantai nilai komoditas jagung serta strategi peningkatan pendapatan petani jagung di Propinsi Gorontalo. Penelitian MP3EI 2011-2025). Gorontalo: Lemlit UNG.Junaidi, J., Amir, A., & Hardiani, H. (2014). Potensi klaster agroindustri usaha mikro kecil dan menengah di Provinsi Jambi. Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2(1), 9-20.kajian kebijakan agribisnis komodistas unggulan daerah di Provinsi Gorontalo, Balai Pengkajian Teknologi Pertanian (BPTP) Gorontalo, 2012Kementerian Koordinator Bidang Perekonomian Republik Indonesia: Masterplan percepatan dan perluasan pembangunan ekonomi Indonesia 2011-2025: Jakarta: 2011Mubyarto, 1984. Strategi pembangunan pedesaan. Yogyakarta: P3PK UGM.Ruslan, M. dan Anwari WMK. 2006. Pemberdayaan masyarakat – mengantar manusia mandiri, demokratis dan berbudaya. Khanata.Sjahrir dan Koreten, 1988. Pembangunan berdimensi kerakyatan. Jakarta. Yayasan Obor Indonesia.Suyono, Haryono dan Haryanto, R. 2007. Pedoman pembentukan dan pengembangan pemberdayaan keluarga – POSDAYA.Balai Pustaka.Renstra Dinas Pertaniandan Ketahanan Pangan Provinsi Gorontalo 2012-2017Sutomo. 2009. Pembangunan masyarakat. Yogyakarta. Pustaka Pelajar.Tesoriero, Frank, Jim Ife. 2008 Community development. community based alternatives in an age of globalisation. Yogyakarta. Pustaka Pelajar